Contextualization of Zhihar Based on Tafsir Literature In the Communication Relationship between Husband and Wife - Eka Putri, Nerisma (Universitas Muhammadiyah Surabaya, 2024)
Abstract: In marriage, Allah swt legalizes the relationship between husband and wife, with the husband having to keep good words in order to avoid words that hurt his wife. Especially if the husband utters zhihar to his wife. In the Jahiliyyah era, zhihar was considered a divorce, then Islam canceled it with the rule that the husband was prohibited from mixing with his wife before paying expiation. The origin of the terminology of zhihar was due to the issue of a woman named Khaulah bint Tsa´labah who had been zhihar by her husband Aus ibn Shamit, Aus said to his wife: